1992
DOI: 10.1063/1.462825
|View full text |Cite
|
Sign up to set email alerts
|

Selective bond fission in methyl mercaptan at 193 nm via radial derivative coupling between the 2 1A″ and 1 1A″ adiabatic electronic states

Abstract: We investigate the origin of the observed fission of the stronger S–H bond over the weaker C–S bond in CH3SH excited at 193 nm using the complementary techniques of mass-resolved photofragment time-of-flight spectroscopy and emission spectroscopy. The velocities and angular distributions of the CH3S and SH photofragments show that both C–S and S–H bond fission occur on a subpicosecond timescale and impart considerable energy to relative product translation. The dispersed emission from photoexcited CH3SH molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…The result is consistent with previous theoretical and experimental work. 4,5,8,[15][16][17] For the inner part of the v 2 = 0 image, a set of finely structured rings were observed as shown in Fig. 2A and 1A.…”
Section: (1) Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The result is consistent with previous theoretical and experimental work. 4,5,8,[15][16][17] For the inner part of the v 2 = 0 image, a set of finely structured rings were observed as shown in Fig. 2A and 1A.…”
Section: (1) Introductionmentioning
confidence: 97%
“…The highly anisotropic photofragment angular distributions measured in crossed laser-molecular beam experiments 4,5 show that both C-S and S-H fission processes occur on a sub-picosecond time scale upon excitation in both the first and second absorption bands. Using H Rydberg atom photofragment translational spectroscopy, Wittig and co-workers 7 confirmed that the partner CH 3 S fragments formed in the 248 nm photolysis of CH 3 SH are vibrationally cold, while those formed as a result of photolysis at 193 nm carry high (up to v = 17) levels of C-S stretching excitation.…”
Section: (1) Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, when the molecule is excited at 193 nm in the higher energy absorption band, it is promoted to the upper bound adiabat-the 2 1 A surface-where it dissociates via nonadiabatic coupling to the transition state region of the lower adiabat. Photofragment velocity and angular distribution measurements on CH 3 -S-H at 193 nm show that the nonadiabatic decay to the transition-state region of the lower surface occurs in less than a picosecond and results in a factor of eight larger branching for decay of the transition state complex to the CH 3 + SH exit channel than direct excitation to the lower adiabat at 222 nm (90)(91)(92). The larger branching ratio results from the stretching of the C-S bond on the upper adiabat, evidenced in emission spectroscopy experiments (93).…”
Section: Probing Nonadiabatic Effects At the Transition Statementioning
confidence: 99%
“…The UV photodissociation dynamics of CH 3 SH has been extensively investigated previously [2][3][4][5][6][7][8][9]. Experimental and theoretical results indicate that photodissociation of CH 3 SH in the UV region occurs primarily through the direct fission of the S-H bond via a perpendicular electronic excitation.…”
Section: Introductionmentioning
confidence: 99%